O-Ataraxia Youth Community Space With Freedom Concept - Ayu Nisrina Hanif (Jurnal Poster Pirata Syandana, 2023)
Many youth communities have acquired urban spaces for activities. This can be seen in several phenomenon, one of which is Citayam Fashion Week. Based on existing communities in Indonesia, communities that use urban spaces for activities such as fashion, skateboarding, roller skate, BMX, graffiti, music, photography-videography, and shopping. These communities need to be accommodated by providing a space for young people as a creative public space that gives them freedom of expression. The preparation of a space program with the creative design method is highly emphasized in this design by compiling several space searches/mapping.